Level of prejudiced among youth in Klang Valley, Malaysia towards public transport - Dahalan, Dzuhailmi; Alby, Jeffrey Lawrence D'Silva; Abdullah, Haslinda; Ahmad, Nobaya; Ismail, Ismi Arif (Marsland Press, 2014)
Psychological constructs are undeniably pertinent in influencing users’ willingness to choose public transport as their primary means of getting around. The aim of this article is to determine the level of prejudice among urban youth in Klang Valley, Malaysia towards public transport. This study involved a total of 445 respondents living in Klang Valley. In general, this study showed that the level of prejudice of youth in Klang Valley towards public transport is moderate. Significant differences were noted in terms of prejudice levels based on gender and ethnicity. The study suggests some ways on how to reduce negative perceptions of public transport among youth.